The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1976
DOI: 10.1104/pp.58.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Native Gibberellins in the Internode, Nodes, Leaves, and Inflorescence of Developing Avena Plants

Abstract: The native gibbereilins (GAs) of various organs of the Avena plant were analyzed by bioassay and gas chromatography-mass spectrometry (GC-MS) after silicic acid partition column chromatography. The major GA of the inflorescence was identified as GA3 by GC-MS, and this GA also forms the major component of the nodes, p-i internode, and roots as determined by GLC or chromatography/bioassay. The inflorescence and nodes are the major sources of native GAs, the last two leaves, internode, and roots having dgnificant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1

Year Published

1977
1977
1986
1986

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…But the level was substantially lower than in young leaves, and it was not at all clear that the intemodes were contributing to GA synthesis. Kaufman et al (21) analyzed the GAs in extracts of various parts of oat plants, Avena, and reported relatively small amounts in young internodes as compared to the inflorescences and nodes. They were also able to show some interesting qualitative changes in the GAs in internodes at different stages of growth.…”
Section: Resultsmentioning
confidence: 99%
“…But the level was substantially lower than in young leaves, and it was not at all clear that the intemodes were contributing to GA synthesis. Kaufman et al (21) analyzed the GAs in extracts of various parts of oat plants, Avena, and reported relatively small amounts in young internodes as compared to the inflorescences and nodes. They were also able to show some interesting qualitative changes in the GAs in internodes at different stages of growth.…”
Section: Resultsmentioning
confidence: 99%
“…1) could include GA1 and/or GA3, and GA19. GA1, GA3, GA4, GA7, and GA19 have all been characterized from various members of the Graminae, and GA19 is native to corn (4,10,11,14,20). Thus, large increases in GA-like activity, particularly of a nonpolar nature, were observed in apical meristems undergoing a sex reversal.…”
Section: Methodsmentioning
confidence: 99%
“…This growth in the nodepulvinus which results in negative geotropic curvative can be enhanced by, and is very sensitive to, auxin application in A vena (13), and in Poa pratensis to Ethephon, and especially Ethephon plus GA3, but not to GA3 alone (25). In A vena, a festucoid grass, the leaf sheath pulvinus (termed node-pulvinus hereafter) is a significant source of GAs, as are elongating internodes and inflorescences (15). During transition from lag to log phases of internodal extension there is a significant increase in more polar GAs (15).…”
mentioning
confidence: 99%